Soil physicochemical properties under pepper farming in Kampung Bantang, Serian - Wong, King Hong (University Malaysia Sarawak, UNIMAS, 2015)
Pepper (Piper nigrum L.) is one of the main crops grown in Malaysia. This study compared the soil physicochemical properties under pepper cultivation at Kampung Bantang. Soil samples were collected from surface soils (0-10 cm) of four study sites, namely, pepper gardens of three different ages (less than one year, two years, five years) and fallow land. The soil analysis revealed that the surface soil of the study sites were clayey and strongly acidic. The total N values were found to be ranged from 1.80 g kg-1 to 4.34 g kg-1. It was also indicated that the available P content at the study sites ranged from 0.00 mg kg-1 to 490.28 mg kg-1. On the other hand, the exchangeable potassium (K) gave the value ranging from 0.09 cmolc kg-1 to 0.99 cmolc kg-1. The available P and exchangeable K were generally higher at fertilizing points than those at non-fertilizing points. From the soil analysis result, it could be deduced that the soil in Kampung Bantang is suitable for pepper cultivation. No significant difference was found for in most of the soil physicochemical properties between pepper farms and fallow land. However, there was nutrient accumulation in soil due to fertilizer application in pepper farms.